Biofortification of rice Oryza sativa L with zinc through nutripriming - Veena Mathew (Department of Botany, University of Calicut, 2025)
Zinc (Zn) is an essential trace element needed by all living organisms for their proper growth, development and reproduction. Deficiency of Zn in human diets constitutes a significant nutritional issue. Biofortification of rice presents a viable and economical approach to enhance Zn intake, especially among populations that primarily consume rice. This study aimed to biofortify rice through nutripriming with Zn compounds (ZnSO4 and ZnNO3) to increase grain Zn content without compromising the yield. A preliminary evaluation of 30 rice genotypes, comprising 15 landraces and 15 elite varieties, was performed to determine their grain Zn content, as well as levels of other micronutrients, phenolics, amylose, anthocyanins, and flavonoids. Based on these observations, four hybrid elite varieties, viz. Annapoorna, Jyothi, Ponmani, and Uma, and four landraces such as Adukkan, Gandhakashala, Kumkumashali, and Mullankayama were selected for further biofortification studies. In these varieties, standardisation of priming concentration and duration for the priming agents ZnSO4 and ZnNO3 were analysed for seed priming and seedling priming. The priming dosage and duration with the priming agents ZnSO4 and ZnNO3 was fixed as 0.5M, 18 h. The dosage of seedling priming was also standardized at 0.5%. Seed and seedling priming in these rice varieties showed an enhancement in growth, yield, and grain Zn content, and the effect was more pronounced with combined seed and seedling priming treatments. The increase in grain Zn content and yield was greater with ZnNO3 priming compared to ZnSO4, leading to the selection of ZnNO3 for further studies. The two rice varieties, Annapoorna and Kumkumashali, were chosen for additional analysis as they demonstrated a more pronounced response to the priming treatments. Priming with ZnNO3 increased photosynthesis, as evident from the enhanced pigment content, photosystem activities, chlorophyll stability index, Chl a fluorescence parameters, and leaf gas exchange parameters. The antioxidative function of the primed plants was improved, as indicated by the activities of superoxide dismutase, catalase, ascorbate peroxidase, and guaiacol peroxidase. Consequently, lipid peroxidation was lower, the levels of superoxide and H2O2 were reduced, and decreased membrane leakage, alongside increased membrane stability, was observed in primed plantscompared to the non-primed control plants. Thus, by enhancing the photochemistry and antioxidant network, the growth and yield of the rice plants were improved in the primed plants. Priming at the seed and seedling stages, along with the additional foliar application of ZnNO3 during critical reproductive stages such as booting, flowering, and the milky stages, enhanced the Zn content, reduced the phytate levels, and increased the bioavailability of Zn in rice grains. Among all the parameters analysed, Kumkumashali performed better than Annapoorna; thus, further analysis was conducted on this plant. Further studies aim to analyse the performance of rice growth, biomass, yield, and grain Zn content, alongside the expression patterns of membrane transporters, such as zinc-regulated iron-regulated transporter-like proteins (ZIP) and heavy metal ATPases (HMA) family genes (OsZIP 1 to 10 and OsHMA2), in root, node I, flag leaf, and panicle under both Zn deficient and sufficient conditions, employing the techniques of seed priming and foliar spray at reproductive stages (booting, flowering, and milky stages). Under Zn deficient condition, the Zn treatments significantly enhanced yield and grain Zn content, including Zn content in various rice tissues, to levels comparable to those observed under the Zn sufficient condition. The various ZnNO3 treatments induced the expression of several transporter genes, such as OsZIP2, OsZIP8 and OsHMA2, particularly under Zn deficient conditions, indicating a crucial role for these transporters in improving Zn uptake, transport, and remobilization in rice. This research illustrated the impacts of seed priming with ZnNO3, highlighting its capacity to enhance agronomic and yield characteristics, along with increasing grain Zn content in subsequent generation of rice. The carryover effects into the subsequent generation indicate that priming imprints could provide a viable approach for enhancing crop nutrition across various growing cycles. Re-priming further amplifies these advantages, suggesting its capacity to support biofortification initiatives in areas experiencing chronic Zn deficiencies. The outcomes of this research are promising for broader adoption in sustainable agricultural practices, paving the way for nutritionally enriched rice production.
Keywords: Biofortification; Foliar Spray; Hidden Hunger; HMA Seed Priming; ZIP.